MODEL PEMBELAJARAN INTERAKTIF (E-LEARNING) UNTUK MENINGKATKAN KETERAMPILAN OPERASI MATEMATIKA (Studi Kasus pada Siswa kelas X/1 IPS SMA Kristen Immanuel Pontianak) - Yanti Yanti; Saparso Saparso (Jurnal Inovasi Penelitian, 2020)
The aim of this research is to find out the use of interactive learning to increase mathematic operation skill of the tenth grade social science students of SMA Kristen Immanuel Pontianak. This is a classroom action research, with the subject of the tenth grade social science students of SMA Kristen Immanuel Pontianak, as many as 39 students. There were 2 research cycles; the first cycle comprised of 6 meetings and the second cycle comprised of 4 meetings. The instruments used to obtain the data needed were the students’ learning result, questionnaire, open-ended essay, pre-test and post-test, observation note among teachers and IT and documentation team. This research shows that the use of interactive learning increases mathematical operation ability compared to conventional learning. This is shown from the increase of the average score and the number of students who showed improvement on their post-test in each cycle. The increase of the average score in the first cycle was 39,1% compared to the pre-test and the increase of the average score in the second cycle was 75,7% compared to the pre-test and was 93,6% compared to the first cycle. The results were solidified by the increase of the number of students who showed improvement on their post-test in the first cycle (92,3%) and the second cycle (97%). Based on the students’ questionnaire and open-ended essay, it is further proven that the students were extremely interested to join the interactive learning. The students themselves also measured the increase of their own mathematical ability during the first and the second cycle. There were 14,7% who answered “increase very significantly”, 79,41% answered “increase significantly”, 5,88% answered “indifferent”. No one answered “does not increase” and “no influence at all”. To conclude, the students who felt their ability increased were 93,58%.